2013
DOI: 10.19026/ajas.5.4847
|View full text |Cite
|
Sign up to set email alerts
|

On-farm Testing of Savanem 20 EC (Ethoprophos) for Control of Plant Parasitic Nematodes Associated with Pepper (<em>Capsicum annuum</em>) in Tillaberi (Niger)

Abstract: The study assessed the effectiveness of Savanem 20 EC (Ethoprophos, 200g/l), a newly introduced nematicide on the plant-parasitic nematodes associated with sweet pepper (Capsicum annuum), the second most important vegetable crop after the onions in Niger. This product was compared with Furadan 5G (Carbofuran). The results show that Savanem 20 EC at the rate of 50 L/ha is more effective than Furadan at the rate of 40 kg/ha in suppressing population of Meloidogyne spp. and reducing the root gall index. Despite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…The study further established that cultivated soil in Abua is vulnerable to nematode infestation and crop plants growing on it have narrow chances for high performance. Adamou et al (2013) reported that pepper is susceptible to nematode infestation, and its actions on the crop can be compounded by poor care system by the farmer. Coyne et al (2003) suggest that thirty percent of total crop loss resulting in food insecurity in Africa can be attributed to damages due to nematode infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…The study further established that cultivated soil in Abua is vulnerable to nematode infestation and crop plants growing on it have narrow chances for high performance. Adamou et al (2013) reported that pepper is susceptible to nematode infestation, and its actions on the crop can be compounded by poor care system by the farmer. Coyne et al (2003) suggest that thirty percent of total crop loss resulting in food insecurity in Africa can be attributed to damages due to nematode infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Meloidogyne spp. are considered the most important group of phytonematodes due to their considerable damage occurred for plants (Ibrahim et al, 2010;Anwar, 2006;Anwar and Mckenry, 2010;Shakeel et al, 2012;Adamou et al, 2013;Korayem et al, 2014;Korayem and Youssef, 2015;Singh and Khanna, 2015;Kumar et al, 2017;Tariq-Khan et al, 2017 andVindhyarani, 2017;El-Nuby et al, 2019;Basyony et al, 2020). The biodiversity of indigenous plant parasitic nematode communities can play an important role in the adaption and success of a new species in specific area, since native nematodes could be potential antagonists to the invasive one.…”
Section: Introductionmentioning
confidence: 99%